2020
DOI: 10.13057/biodiv/d210743
|View full text |Cite
|
Sign up to set email alerts
|

Review artitle Review: Traditional ecological knowledge of tribal communities of North East India

Abstract: Abstract. Tynsong H, Dkhar M, Tiwari BK. 2020. Review: Traditional ecological knowledge of tribal communities of North East India. Biodiversitas 21: 3209-3224. Traditional ecological knowledge (TEK) refers to the knowledge, innovations and practices of indigenous and tribal people relating to the understanding of structure and functioning of neighboring natural ecosystems and their use for human welfare. In this paper, we have reviewed the literature relating to TEK held by the tribal and other traditional soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Various researchers has accounted the social and cultural values of agro-ecological systems using IEK as in India (Das et al, 2012;Harisha et al, 2015;Pandey et al, 2017;Tynsong et al, 2020); and in other countries (Halim et al, 2012;Boafo et al, 2016aBoafo et al, , 2016bChristina et al, 2017). IEK and related practices for various direct and indirect uses of wild plant resources and for other purposes such as weather forecasting, medicinal use of wild plants by tribes ensure promotion of cohesion between the ecosystem and human well-being (Harisha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers has accounted the social and cultural values of agro-ecological systems using IEK as in India (Das et al, 2012;Harisha et al, 2015;Pandey et al, 2017;Tynsong et al, 2020); and in other countries (Halim et al, 2012;Boafo et al, 2016aBoafo et al, , 2016bChristina et al, 2017). IEK and related practices for various direct and indirect uses of wild plant resources and for other purposes such as weather forecasting, medicinal use of wild plants by tribes ensure promotion of cohesion between the ecosystem and human well-being (Harisha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…IEK and related practices for various direct and indirect uses of wild plant resources and for other purposes such as weather forecasting, medicinal use of wild plants by tribes ensure promotion of cohesion between the ecosystem and human well-being (Harisha et al, 2015). Moreover, tribal through IEK make cultural adjustment to bio-physical surroundings for proper resources management (Tynsong et al, 2020) such as Alder Based Agro-forestry System, a IEK based agricultural practices since time immemorial by indigenous tribes of Nagaland, India (Das et al, 2012), where root nodule of alder trees facilitates soil fertilization and the roots prevents soil erosion in slopes (Rathore et al, 2010;Das et al, 2012). Moreover, indigenous forest management by the local people are based on social justice and equity (Geronimo et al 2016) and contributes to water availability, livelihood, biodiversity conservation and health care of the people (Halim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant platforms to adopt, redefine and integrate these knowledge systems and mainstreaming them to policies and programs are critical in safeguarding these potentially sustainable food systems for improved nutrition in indigenous communities [69,70]. Additionally, studies have shown that mainstreaming neglected IFs into nutrition and agricultural policies and programs may revive IF systems and improve household income, food security, dietary diversity and micronutrient intake of women and children [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Records also exist of the use of indigenous knowledge in food production. [54] For example, a 700-year-old indigenous regenerative soil management system that is currently practiced in West Africa in which targeted waste disposal transformed highly weathered low-quality tropical soils into fertile, carbon-rich soils that contributed nearly a quarter of a farm household's income albeit covering a relatively small area while also offering a carbon sequestration solution has been described. [55] Integrating current digital agricultural technologies and methodologies with indigenous knowledge will bring the complementary benefits of both worlds into optimally developing an African agriculture that is resilient, agile, adaptable, and regenerative, thus sustainable.…”
Section: Leveraging Indigenous Knowledgementioning
confidence: 99%
“…[ 51 , 52 , 53 ] Records also exist of the use of indigenous knowledge in food production. [ 54 ] For example, a 700‐year‐old indigenous regenerative soil management system that is currently practiced in West Africa in which targeted waste disposal transformed highly weathered low‐quality tropical soils into fertile, carbon‐rich soils that contributed nearly a quarter of a farm household's income albeit covering a relatively small area while also offering a carbon sequestration solution has been described. [ 55 ]…”
Section: Leveraging Indigenous Knowledgementioning
confidence: 99%